How do entrepreneurs create indirect network effects on digital platforms? A study on a multi-sided gaming platform - Ojala, Arto; Lyytinen, Kalle (Routledge, 2022)
Digital platforms play a central role in today’s market-based competition. To build a successful platform, entrepreneurs must pursue indirect network effects and shape multiple sides of the platform. However, the extant literature provides only a meager understanding of how entrepreneurs can create such indirect network effects. To better understand how this can be done, we conduct a case study that longitudinally traces 16 years of digital game platform growth as the entrepreneurs bring the platform successfully into multiple markets. The analysis advances theorising of the entrepreneurs’ repertoires of moves seeking to increase the number and variety of platform participants conducive to creating indirect network effects. The findings indicate that early moves focus on creating technical solutions that overcome technical challenges and permit platform scaling, whereas later moves seek to create a more flexible and generalisable platform architecture that allows a wider range of interactions. The findings make several contributions to the digital entrepreneurship literature by synthesising a dynamic model of entrepreneurs’ repertoire of competitive moves that will induce indirect network effects.
Keywords: Innovation; Architecture; Strategies; Developers; Logic; Moves; fi=Kansainvälinen liiketoiminta|en=International Business|